The Comics Page: Scholarly Books Briefly Noted (2017–2018). Issue 1 (29th June 2018) - Priego, Ernesto
Abstract : This article documents a selection of scholarly books received by The Comics Grid: Journal of Comics Scholarship during the 2017–2018 editorial year and notes them briefly, collating their metadata and publisher's blurbs, as well as hyperlinks to the respective publisher's web pages for each book. This round-up seeks to promote awareness of these recent publications within comics scholarship, and to encourage their acquisition by academic libraries, academic review and, if appropriate, inclusion in syllabi.